2022
DOI: 10.3390/diagnostics12102523
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Ultrasonography for Imaging Pediatric Fat Pad Herniation through the Lateral Patellar Retinaculum

Abstract: A 3-year-old boy was found to have a painless mass over his right anterior lateral knee for the previous 6 months. The mass was hardly identified during knee extension and became visible upon squatting. There was no specific finding on ultrasound imaging over his right knee at the supine extended position. During squatting, ultrasound imaging showed an ill-demarcated hyperechoic mass protruding next to the cartilage overlying the distal femur towards the subcutaneous layer through a slit over the lateral patel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Moreover, dynamic scanning can also be used to visualize a snapping or an abnormal displacement of the fat pads of the knee. 6…”
Section: Impingement and Intraarticular Loose Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, dynamic scanning can also be used to visualize a snapping or an abnormal displacement of the fat pads of the knee. 6…”
Section: Impingement and Intraarticular Loose Bodymentioning
confidence: 99%
“…Dynamic scanning with joint/probe movements also allows for better visualization by mobilizing the fluid/edema content (Videos 4 and 5, http://links.lww.com/PHM/B910 and http://links.lww.com/PHM/B911). Moreover, dynamic scanning can also be used to visualize a snapping or an abnormal displacement of the fat pads of the knee 6 …”
Section: Anterior Viewmentioning
confidence: 99%
“…Mezian et al [18] described a unique case where ultrasound imaging played a crucial role in diagnosing and surgically managing a nonanatomic repair of ankle extensor tendons after a penetrating injury. Wu et al [19] reported a case of a child with a lateral patellar retinaculum defect in pediatric knees, diagnosed through dynamic ultrasound. This case underscored the usefulness of ultrasound examination in pediatric knee problems and its ability to capture the exact "pathological moment" through dynamic scanning.…”
mentioning
confidence: 99%